Kinetics of Thermal Decomposition of Potassium Sodium Tartrate Tetrahydrate - Wang, Xinfang (Asian Journal of Chemistry, 2012)
Kinetic analyses were performed on potassium sodium tartrate tetrahydrate (KNaC4H4O6·4H2O) using TG/DTA measurement in N2. The thermal behaviour and the effect of heating rate on the kinetics were investigated. To estimate the activation energy E of decomposition, the Ozawa and Kissinger iso-conversional method were applied. All stages of dehydration are governed by nucleation model F1 [g(a) = (1-a)-1].